Skin autofluorescence is an independent predictor of post stroke infection in diabetes - Filipov, Alexandra; Fuchshuber, Heike; Kraus, Josephine; Ebert, Anne; Sandikci, Vesile; Alonso, Angelika (Journal of stroke and cerebrovascular diseases, 2021)
Post stroke infection occurs in 15-20% of acute stroke patients and is associated with a poor longterm outcome. In a prospective study on 113 acute ischemic stroke patients with diabetes mellitus 15.9% suffered nosocomial infection. We found chronic hyperglycemia measured by skin autofluorescence in arbitrary units to be an independent predictor of a nosocomial infection post stroke (OR=3.24 [CI 95%: 1.13; 9.26], p=0.029). Skin autofluorescence represents the glycemic memory beyond HbA1c. Potential mechanisms leading from increased skin autofluorescence to vulnerability for infectious complications include more severe strokes due to preexisting vasculopathy and exacerbated post stroke immunosuppression.
Gesehen am 07.09.2021